PENGARUH PEMBELAJARAN COOPERATIF LEARNING TYPE MAKE A-MATCH TERHADAP HASIL BELAJAR IPA KELAS V SDN 01 MANISREJO KOTA MADIUN - Ibadullah Malawi; Juwarti Juwarti (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2012)
The objectives of this research was to measure the influence of cooperative learnig type make a-match towards studets’ achievement in Natural Science. This research was conducted at SD Negeri 01 Manisrejo, Madiun Municipality, term 2011/2012. The analysis concluded that: (1) students’ achievement of the experiment class with cooperative learnig type make a-match  was better than that of the control class with conventional model; and (2) the learning activity showed that the students with make-a-match model were more greatly interested in the learning process being more couragious, where students not only studied but also playing games, which entailed the better students’ achievement than those with conventional model who have become very passive.